Logistic regression analysis for awareness among students towards environmental care in UiTM, Tapah Campus / Faridah Zulkipli, Nurul Husna Jamian and Ilya Zulaikha Zulkifli - Zulkipli, Faridah; Jamian, Nurul Husna; Zulkifli, Ilya Zulaikha (Universiti Teknologi MARA, Perak, 2019)
Solid waste management is increasing and become one of the crucial environmental issues in Malaysia. However, individuals nowadays have lack aware in achieving sustainability in waste management that contributes for current and future generations. The information related to this environmental issue need to be shared among publics especially students in order to educate them and to create positives vibes towards environment. Therefore, this study sought to investigate the contribution factors such as gender, knowledge, perceptions, practice, and attitude towards awareness level among students. A set of data primarily collected using direct questionnaires among students from the Faculty of Computer and Mathematical Sciences. A total of 354 students comprising from various program were response and the data was analyzed using Logistic regression. The results found that four variables such as gender, knowledge, perceptions, and attitude were significantly influence the level of awareness among students towards environmental care.